Tailorable biosensors for real-time monitoring of stress distribution in soft biomaterials and living tissues - Fenghou Yuan; Huitang Qi; Binghui Song; Yuntian Cui; Junsheng Zhang; Huan Liu; Bo Liu; Hai Lei; Tian Liu (Nature Communications)
Abstract Visualizing mechanical stress distribution in soft and live biomaterials is essential for understanding biological processes and improving material design. However, it remains challenging due to their complexity, dynamic nature, and sensitivity requirements, necessitating innovative techniques. Since polysaccharides are common in various biomaterials, a biosensor integrating a Förster resonance energy transfer (FRET)-based tension sensor module and carbohydrate-binding modules (FTSM-CBM) has been designed for real-time monitoring of the stress distribution of these biomaterials. By simple dripping or soaking, FTSM-CBM enables fast, reproducible and semiquantitative detection of both 2D and 3D stress distributions in polysaccharide-based hydrogels. Additionally, it provides valuable information such as microstructure hints and fracture site warnings. FTSM-CBM can also monitor the locomotion of maggots, which is not feasible with most existing techniques. Furthermore, by changing the CBM, FTSM-CBM can be expanded for various polysaccharide-based biomaterials. This study provides a powerful tool that may promote related research in life and materials science.